Interactive effects of testosterone and the androgen receptor CAG repeat length polymorphism on cardiovascular‐renal events and mortality in men with diabetes. Issue 1 (23rd October 2018) - Wong, Poon‐Wing; Lee, Heung‐Man; Lau, Eric S.H.; Lim, Cadmon; Ma, Ronald C.W.; Kong, Alice P.S.; Chan, Juliana C.N.; Luk, Andrea O.Y.
Abstract: Aim: Current evidence relating testosterone to cardiovascular disease and mortality is inconclusive. Cellular effects of testosterone are mediated by androgen receptor and longer receptor gene CAG repeat length correlates with reduced transcriptional activity. We investigated the independent and interactive association of total testosterone and CAG repeat length with incident cardiovascular disease (CVD), chronic kidney disease (CKD) and mortality in Chinese men with type 2 diabetes. Materials and methods: From March 2008 and February 2009, 474 men with diabetes underwent structured clinical assessment including genotyping for CAG repeat length. Patients were followed for new‐onset CVD, CKD defined by estimated glomerular filtration rate <60 mL/min/1.73m 2, and death until 31 May 2015. Results: In this cohort (mean age: 58.6 years, disease duration: 15.4 years), CAG repeat number ranged from 11 to 32 with median of 23, and 9.3% had low testosterone. Over follow‐up of 5.8 years, 49 (10.3%) men had CVD, 139 (29.3%) had CKD, and 43 (9.1%) died. In multivariate Cox regression adjusted for age, duration of diabetes, and cardiometabolic risk factors, both total testosterone and interaction term of total testosterone × CAG repeat were associated with all‐cause death with respective hazard ratios 1.63 ( P = 0.002) and 0.98 ( P = 0.004). Total testosterone and CAG repeat were not related to incident CVD or CKD. Conclusions: Among men with type 2 diabetes, high total testosterone was associated with increased mortality in the presence of shorter CAG repeat length but decreased mortality in those with long CAG repeats.